Student Continued Engagement in Taekwondo Activity in Selected Colleges and Universities: A Self-Determination Theory-Based Process Model - Catapang, Jonathan P.; Gonzales, Rizzenellie P.; Ayo, Eliza B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Self-Determination Theory (SDT) provides a comprehensive framework for understanding student motivation and engagement through three psychological needs: autonomy, competence, and relatedness. While extensive research has examined SDT in traditional academic contexts, limited investigation has explored its application to martial arts education, particularly Taekwondo. This study examined the relationship between SDT constructs and student engagement in Taekwondo activities among college students. A cross-sectional survey design was employed with 125 Taekwondo practitioners (107 females, 18 males) from selected colleges and universities. Participants completed a multi-item Likert scale measuring four SDT constructs: autonomy, competence, relatedness, and motivation, with five items per construct. Data analysis included descriptive statistics, independent samples t-tests, one-way ANOVA, and multiple linear regression. Results revealed that relatedness scored highest among participants (M = 4.18), followed by competence (M = 3.73), motivation (M = 3.22), and autonomy (M = 2.98). No statistically significant differences were found between genders or across sleep hour categories. Interestingly, parental involvement significantly affected motivation, with students reporting low parental involvement demonstrating higher motivation levels than those with medium involvement. Multiple regression analysis revealed that all three SDT needs significantly predicted motivation, with competence emerging as the strongest predictor (β = 0.394), followed by relatedness (β = 0.313) and autonomy (β = 0.234). The model explained 50.7% of the variance in student motivation (R² = 0.507). These findings suggest that Taekwondo training environments that foster feelings of competence, social connection, and appropriate autonomy support can enhance student engagement and sustained participation in Taekwondo activities.